Multifunctional Nanocomposites in the SiC-Al\(_2\)O\(_3\)-SIALON System for Armor Plates, Turbine Blades, High-Temperature and Wear-Resistant Nodes - Z. Kovziridze; N. Nijaradze; G. Tabatadze; M. Mshvildadze; N. Daraxvelidze; Z. Mestvirisvili; V. Kinkladze (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
The goal of the study is to obtain the composite in the SiC-Al203-SiAlON system with the metal-thermal method in the nitrogen medium. Methods: SiALON-s are solid metal oxide solutions in nitrides. The area of their presence is considered in a four-component system - Si3N4-ALN-AL2O3-SiO2. In the present paper SiALON-containing composite was obtained through an alum-thermal process in the nitrogen medium on the base of Geopolymer (kaolin and pology cley – Ukraine), SiC, aluminum nano-powder and Si powder with additives of perlit (Aragatz, Armenia) by the reactive baking method. The advantage of this method is that compounds, which are newly formed thanks to interaction going on at thermal treatment: Si3N4, Si, AlN are active, which contributes to SiALON formation at relatively low temperature, at 1250-1300°C. It is evident that inculcation of ALN in the crystal skeleton of ß-Si3N4 is easier since at this temperature interval crystal skeleton of Si3N4 is still in the process of formation. Results: ß-SiAlON was formed at the sintering of SiC-aluminum and silicium powder, geopolymer at 1450°C. The porosity of carbide SiAlON composite obtained by reactive sintering, according to water absorption, equals 13-15%. The samples were fragmented in a jaw-crusher and were powdered in an attrition mill till micro-powder dispersion was obtained. Then samples were hot-pressed at 1620°C under 30 MPa pressure. Hold-time at the final temperature was 8 min. Sample water absorption, according to porosity, was less than 0.5%. Further studies were continued on these samples. It should also be stated that the strength and wear resistance of SiALONs increase in their presence in silicium carbamide-containing composites. Conclusion: The paper offers processes of formation of SiC-SiAlON and Al2O3-SiAlON composites and their physical and technical properties. The phase composition of the composites was studied by X-ray diffraction method, while the structure was studied by the use of optic and electron microscopes. Obtained materials are used in protecting jackets of thermocouples used for melted metal temperature measuring (18-20 measuring), for armor plates, turbine blades and blades, high-temperature and wear-resistant for nodes and for constructions used for placing objects in factory furnaces. The mechanical modulus of materials was calculated according to the formula of Z. Kovziridze.